PENENTUAN PRIORITAS PENGENDALIAN PERSEDIAAN PADA INDUSTRI MAKANAN PAGI DI KOTA PEKANBARU MENGGUNAKAN KLASIFIKASI ABC - Rahmadini Payla Juarsa; Ariandini Simalongo; Shiva Ainda Firdaus; Gilbert Ernest Siburian (Fakultas Pertanian Universitas Riau, 2023)
The breakfast food industry was a micro, small, and medium enterprise that produced various preparations for breakfast. The products produced were yellow noodles, leaf lontong, plastic lontong, fried tofu, and peanut sauce. The breakfast food industry did not have a system for prioritizing inventory control. As a result, the industry often experienced stock shortages when demand was high and excess stock when demand was low. Therefore, this research aimed to identify and classify products using the ABC classification method to obtain product classes that required special attention to avoid shortages or excess inventory. ABC classification was a method of classifying objects based on their profit value. Products with more excellent profit value were given the highest priority so that they were always ready to be produced and always had stock. This research used data on the number of sales and product prices in the breakfast food industry in 2022. The research results showed that yellow noodles and leaf lontong were included in class A, plastic lontong was included in class B, and fried tofu and peanut sauce were included in class C. The products included in class A needed high priority because they contributed more than 75% of the total industrial profits. Meanwhile, products belonging to class B got medium priority, and products in class C got low priority for inventory control.